(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The present work aims at understanding the contribution of all sections of women towards the freedom struggle of India in accordance with the nationalist approach. As the available sufficient research material required to examine their role as per different streams, this research work is an humble attempt to examine how the women and students, as pioneers, played a vital role in the same context. Whether they were part of urban educated elite class or illiterate traditions bound or patriarchy bound rural women all of their multifact activities have been thoroughly analysed.